Pemanfaatan Media Pembelajaran Berbasis Etnomatematika dalam Meningkatkan Pemahaman Peserta Didik di Sekolah Dasar (International Forum of Researchers and Lecturers, 2024)
This research aims to analyze the use of ethnomathematics-based learning media in improving students' understanding in elementary schools. Using the Systematic Literature Review (SLR) method, this research identifies, evaluates and synthesizes relevant research results on related topics. The literature selection process was carried out systematically through searches in various accredited scientific journal databases, using certain keywords related to ethnomathematics, learning media, and basic education. The research results show that ethnomathematics-based learning media is effective in increasing students' understanding of mathematical concepts through a contextual approach that utilizes local culture as a learning aid. This approach not only increases mathematical understanding, but also strengthens the link between mathematics learning and local wisdom. This research also reveals the importance of innovative learning media that suit regional cultural characteristics and student needs.